Smoking and Cardiac Structure and Function in the Elderly: The ARIC Study (Atherosclerosis Risk in Communities). (September 2016) - Nadruz, Wilson; Claggett, Brian; Gonçalves, Alexandra; Querejeta-Roca, Gabriela; Fernandes-Silva, Miguel M.; Shah, Amil M.; Cheng, Susan; Tanaka, Hirofumi; Heiss, Gerardo; Kitzman, Dalane W.; Solomon, Scott D.
Abstract : Background—: Cigarette smoking has been associated with higher risk of incident heart failure independent of coronary artery disease, but the impact of tobacco use on cardiac structure and function in the general population is uncertain. This study evaluated the relationship between smoking and echocardiographic measures in a large elderly cohort. Methods and Results—: We studied 4580 participants free of overt coronary artery disease, heart failure, and significant valvular disease from the fifth visit of the ARIC study (Atherosclerosis Risk in Communities) who underwent transthoracic echocardiography. Participants were classified into 3 categories based on self-reported smoking habits: never (43.2%), former (50.5%), and current smokers (6.3%). Pack-years and years of smoking were also estimated. Compared with never smokers, current smokers had greater left ventricular (LV) mass index (80.4±1.1 versus 76.7±0.4 g/m 2 ; P <0.001), LV mass/volume ratio (1.93±0.03 versus 1.83±0.03 g/mL; P <0.001), higher prevalence of LV hypertrophy (15% versus 9%; P =0.008), and worse diastolic function, as reflected by higher E/E′ ratio (11.7±0.2 versus 10.9±0.1; P <0.001), after adjusting for potential confounding factors. In contrast, former smokers showed similar echocardiographic features when compared with never smokers. Furthermore, estimated pack-years and years of smoking, measures of cumulative cigarette exposure, were associated with greater LV mass index, LV mass/volume ratio, and worse diastolic function (higher E/E′ ratio) in current smokers after multivariable analysis (all P <0.01). Conclusions—: Active smoking and cumulative cigarette exposure were associated with subtle alterations in LV structure and function in an elderly, community-based population free of overt coronary artery disease and heart failure. Abstract : Supplemental Digital Content is available in the text.